METALOGIC DIVERSITY OF THE VOLNOVAHSKAYA ORE AREA IN CONNECTION WITH FEATURES OF UKRAINIAN SHIELD LITHOSPHERE'S DEEP STRUCTURE - Kalashnyk, G.; Кuzmin, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the study is to identify new patterns of formation deposits and ore occurrences of different metallogenic specialization in the Volnovakhskaya ore zone of junction of the Priazovsky megablock of Ukrainian Shield with the Donbas in connection with the nature of the deep structure of lithosphere. The analysis of geophysical, geological, petrological and radiogeochemical information on the specifics of the formation, placement of the main types of deposits and ore occurrences at the junction of the Priazovsky megablock of the Ukrainian Shield with the Donbas in close connection with the features of the deep structure of the lithosphere, asthenosphere and fault tectonics was carried out. The features of the deep structure of the lithosphere and their physical parameters that affect the conditions of metallogenic diversity and intensive ore genesis in the formation of deposits and ore occurrences of various metallogenic specializations in the Volnovakhskaya ore zone were revealed. The analysis of metallogenic specialization of the main manifested area of research stages of tectonic activation was carried out. We have obtained new patterns in the formation of different deposits and ore occurrences in junction zone of the Priazovsky megablock of the Ukrainian Shield and the Donbas, including uranium ore occurrences. In particular, their connection with the focal structures of repeated magmatism of various composition, hydrothermal activity, halos of secondary metasomatic changes of host rocks within the deep faults and their crossing points over the zone of abrupt change in thickness of the lithosphere of the slope of the Ukrainian Shield, and the formation of barogradient zones in the asthenosphere in the process of the Earth's evolution. The practical significance of this research is to increase the efficiency of metallogenic forecasts by expanding the range of metallogenic diversity and intensity of ore genesis, geophysical and petro-geochemical indicators of primary scale concentration of ore components of different metallogenic specialization in the asthenosphere. This makes it possible to reasonably determine the prospects of the territories for the possibility of forming large ore concentrations of different metallogenic specialization with the allocation of areas of their most probable localization.
Keywords: lithosphere; metallogenic diversity; intensive ore genesis; the junction zone of the Priazovsky megablock and the Donbas; Volnovakhskaya ore zone